A lipophilic, fluorine-free, thermostable, inexpensive, S4-symmetric, highly soluble, weakly coordinating, protolabile aluminate - Straub, Bernd Franz; Wrede, Michael; Schmid, Karin; Rominger, Frank (European journal of inorganic chemistry, 2010)
This communication presents the facile and cost-effective synthesis as well as properties of salts of a lipophilic aluminate anion. Its unprecedented solubility in pentane makes possible tetrabutylammonium salt extraction with pentane. Nevertheless, its symmetry leads to high melting points of its thermostable salts. Several single crystals for X-ray diffraction studies have been obtained. The anion is devoid ofhalogens, but is stable against sterically demanding electrophiles such as the trityl cation. However, it is unstable in protic media and hydrolyzes in the presence of water within days.
Gesehen am 01.09.2023